494 Comparison of Disc Height Restoration and Subsidence Rates Between Static Versus Expandable Titanium Cages for Lateral Lumbar Interbody Fusion. (April 2023) - Ashayeri, Kimberly; Neifert, Sean N.; Frempong-Boadu, Anthony; Protopsaltis, Themistocles; Lau, Darryl
Abstract : INTRODUCTION: It has been shown that expandable cages for transforaminal lumbar interbody fusion (TLIF) are associated with increased rates of subsidence. However, as lateral lumbar interbody fusion (LLIF) cages offer substantially larger footprints, this may offset the risks. METHODS: A retrospective review was performed of a consecutive adult patients undergoing LLIF with either static or expandable cages from 2013-2021. Demographics and surgical details were collected. Posterior disc height (PDH), subsidence, and fusions status were compared between patients with static and expandable cages. Follow-up were reported at minimum 6-months and 1-year. RESULTS: A total of 120 patients had 173 cages implanted: 96 patients with 143 static cages vs. 24 patients with 30 expandable cages. Mean age was 63.4 and 62.4% were male. There were no significant differences in age, gender, BMI, smoking, or osteoporosis. Overall, PDH was significantly increased following LLIF (4.1 v 7.4 mm, p < 0.001). Static and expandable cage types had similar magnitude (3.7 v 3.3 mm, p = 0.311) and percentage (89.0% v 121.5%, p = 0.127) change in PDH, respectively. Overall incidence of cage subsidence at 6-months and 1-year was 6.9% and 10.4% respectively. There was no significant difference in subsidence rates between cage types at 6 months (7.0% v 6.7%, p = 0.949) and 1-year (11.2 v 6.7%, p = 0.461). Radiographic evidence of fusion was present in 92.7% of cases at 1-year, and both cage types achieved similar fusion rates as well (92.2% v 95.6%, p = 0.555). CONCLUSIONS: LLIF static and expandable cages offer similar PDH restoration depending on surgical goals. Expandable cages seem to be less prone to subsidence than smaller TLIF cage counterparts and offer similar fusion rates to static cages. Larger cohort studies are warranted to further validate these findings which are ongoing.